Non Performing Financing dan Dana Pihak Ketiga: Pengaruhnya Terhadap Laba Bank Syariah di Indonesia - Ritonga, Iskandar (Proceedings of Annual Conference for Muslim Scholars, 2019)
This paper undertakes a survey of the sharia banking case studies on Non Performing Financing (NPF), saving and time deposit. The aim is to provide an understanding of the multiplier and also forecast the Return On Asset (ROA). Hence, to accomplish this provide, the quarterly data from the best six sharia bank in Indonesia were analyzed. This study employs multiple regressions analysis.The result shows that the return on asset of Indonesian sharia banking positively supported by saving. The negative effect on ROA areshown by time deposit and NPF.